Farmers' Strategies In Dealing with The Low Selling Price Of Fresh Fruit Bunches In Indragiri Hilir Regency - Mulono Apriyanto; Yulianti Yulianti; Marlina Marlina (Tropical Plantation Journal, 2022)
This study aims to identify the strategies adopted by farmers in Indragiri Regency in response to the low prices for fresh fruit bunches (FFB). The data used are primary data obtained from direct interviews with respondents and secondary data obtained from the literature and institutions related to the topic. This research employs a mixed methodological approach. Data analysis involves collecting data and analyzing quantitative data in the first stage, then collecting data and analyzing qualitative data in the second stage, and finally analyzing the overall data and drawing conclusions from the analysis of the data. Data reduction, data presentation, and conclusion drawing are the methods of analysis.The results revealed the following adaptation strategies: (1) an active strategy, becoming an oil palm farm laborer and opening a side business; (2) a passive strategy, utilizing home yards to grow horticultural crops, borrowing money from tauke, and borrowing / borrowing daily necessities from the shop / shop.